2020
DOI: 10.31220/osf.io/cdf9b
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of waste by-products of rose oil production as feedstuff phytonutrients.

Abstract: The aim of this study was to evaluate possibility for valorization of the dry pressed distilled rose petals (DDRP) as a feedstuff phytonutrients in animal husbandry. In connection with the chemical composition and radical scavenging activity of polyphenol complex in rose waste products were studied. The polyphenol composition in dry rose petals, DDRP and waste water after distillation was identified and quantified. The chromatographic analysis was conducted by HPLC-PDA and LC-MS. The experiments were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…This is the case with the waste rose (Rosa Damascena) petals from the rose oil production. Analysis of their composition shows a rich spectrum of more than 30 bioactive compounds with antioxidant properties [11][12][13]. Previous studies report a that the dried distilled rose petals extract (DDRP extract) exhibit and inhibitory effect against oxidation in relatively low concentrations [11,14].…”
Section: Regulation (Ec)mentioning
confidence: 99%
“…This is the case with the waste rose (Rosa Damascena) petals from the rose oil production. Analysis of their composition shows a rich spectrum of more than 30 bioactive compounds with antioxidant properties [11][12][13]. Previous studies report a that the dried distilled rose petals extract (DDRP extract) exhibit and inhibitory effect against oxidation in relatively low concentrations [11,14].…”
Section: Regulation (Ec)mentioning
confidence: 99%
“…Bulambaeva et al (2014) reported a similar trend in cooked sausages with reduced nitrite content. This phenomenon can be explained by the inhibitory effect of the dihydroquercetin against the free radicals (Vlahova-Vangelova et al, 2014), and the chelate effect of the extract of distilled rose petals (Dragoev et al, 2021) manifested in the conditions of thermally initiated lipolysis during the heat treatment of sausages. Thus, in the control sample free fatty acids appear to be reduced (Table 2).…”
Section: Changes In the Lipid Fractionmentioning
confidence: 99%
“…Distilled rose (Rosa damascena Mill.) petals are a waste product of the rose oil industry -the ethanol extract contains more than 20 quercetin and kaempferol glycosides (Dragoev et al, 2021). A combination of extracts as blends of antioxidants has been an area of interest in the last 10 years (Sharma et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Another natural source of polyphenols is dry distilled rose petals (DDRP): a by-product of the rose oil industry. They contain more than 30 polyphenolic compounds (Dragoev et al 2021) and are characterized by antioxidant and antibacterial properties (Baydar & Baydar 2013). Therefore, the aim of this study was to identify the quality changes during frozen storage of m. Longissimus dorsi, m. Semimembranosus and perirenal adipose tissue from lambs fed a diet supplemented by dihydroquercetin or dry distilled rose petals.…”
Section: Introductionmentioning
confidence: 99%